STRATEGI PENGADAAN SARANA DAN PRASARANA PENDIDIKAN: PENDEKATAN KUALITATIF TERHADAP PEMENUHAN KEBUTUHAN SEKOLAH DI WILAYAH TERDEPAN, TERPENCIL, DAN TERTINGGAL (3T) - anjani, meisya (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2026)
The primary goal of facilities and infrastructure management (Sarpra) is to improve the quality of education through the provision of adequate and effective facilities (Asy’ari, 2021; Nurbaiti, 2015). However, efforts to fulfill Sarpra needs in Indonesia often face challenges regarding equity, particularly in the Frontier, Remote, and Disadvantaged (3T) regions. The uneven availability of Sarpra is a major problem in establishing equitable education (Sari, 2025; Jakaria et al., 2019). This qualitative study aims to analyze the adaptive strategies implemented by schools in the 3T regions in executing the planning and procurement functions of Sarpra to overcome the gap in needs fulfillment. Sarpra management functions, including planning, procurement, and utilization, must be implemented optimally despite facing geographical and logistical constraints (Sutisna & Effane, 2022; Sofiah et al., 2017). Through a case study approach, it was found that procurement strategies in 3T areas highly depend on innovation in needs planning (Kholizah et al., 2023) and synergy between government policies (Syahril, 2023; Tuakara, 2025) and collective school efforts. The results indicate that improving the quality of education in 3T regions (Putera & Rhussary, 2018) can be achieved through adaptive, non-conventional procurement strategies oriented toward the priority scale of student needs.